2021
DOI: 10.1186/s12916-021-02008-2
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the evidence from studies with no events in meta-analyses of adverse events: an empirical investigation

Abstract: Backgrounds Zero-events studies frequently occur in systematic reviews of adverse events, which consist of an important source of evidence. We aimed to examine how evidence of zero-events studies was utilized in the meta-analyses of systematic reviews of adverse events. Methods We conducted a survey of systematic reviews published in two periods: January 1, 2015, to January 1, 2020, and January 1, 2008, to April 25, 2011. Databases were searched fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Overall, we screened 18 636 records, and initially identified 456 systematic reviews of adverse events. 9 After a further screening of the full texts, 102 were excluded for having non-randomised studies of intervention and 153 were excluded for not having a pairwise meta-analysis, having fewer than five studies in all meta-analyses, or not reporting 2×2 table data used in meta-analyses (supplementary table 3). As such, 201 systematic reviews were included in the current study (fig 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, we screened 18 636 records, and initially identified 456 systematic reviews of adverse events. 9 After a further screening of the full texts, 102 were excluded for having non-randomised studies of intervention and 153 were excluded for not having a pairwise meta-analysis, having fewer than five studies in all meta-analyses, or not reporting 2×2 table data used in meta-analyses (supplementary table 3). As such, 201 systematic reviews were included in the current study (fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…This article is an extension of our previous work describing methods to deal with double-zero-event studies. 9 A protocol was drafted on 11 April 2021 by a group of core authors (CX, TY, LL, LFK), which was then revised after expert feedback (SV, LZ, RQ, and JZ; see supplementary file). We also record the detailed implementation of this study (supplementary table 1).…”
Section: Protocol and Data Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…The agreement rate was 0.74 in the full-text screening process. The details of excluded studies during the full-text screen process have been documented in our previous work [ 25 ]. According to the minimal requirement, the sample size of the current study could be sufficient.…”
Section: Resultsmentioning
confidence: 99%
“…The current study is one of the series of a project that aimed to improve the evidence-based practice of systematic reviews of adverse events. A protocol of the project was developed in advance ( supplementary file ), which also involves some context referred to the current study [ 25 ]. This study was designed, conducted, and reported follows the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) Statement [ 26 ]; the following domains are not feasible for the current study: 1) Describe any sensitivity analyses (Reason: no need); 2) Indicate the number of participants with missing data for each variable of interest (Reason: no missing data).…”
Section: Methodsmentioning
confidence: 99%